3D printing of multilayered orodispersible films with in-process drying - Elbl, Jan; Gajdziok, Jan; Kolarczyk, Jan (International journal of pharmaceutics, 2020)
The aim of this study was to prepare benzydamine hydrochloride loaded orodispersible films using modified semisolid extrusion 3D printing method. An innovative approach was developed where thin layer of drug loaded dispersion is printed and dried before printing of subsequent layers. Layer-by-layer drying as the in process step improves mechanical properties of films, uniformity of drug content and allows faster preparation of films in compounding settings due to shortening of drying time. Orodispersible films consisted of film forming maltodextrin, sorbitol as a plasticizer and hydroxyethylcellulose as a thickening agent. The height of the digital model showed excellent correlation with the disintegration time, weight, thickness and mechanical properties of prepared films. Drug content, predefined by volume of digital model and concentration of drug in print dispersion, showed excellent uniformity. The modified printing method shows great promise in a compounding production of personalized film dosage forms, and brings in possibilities such as one step preparation of films with compartmented drugs and incorporation of taste masking or release control layers.
Keywords: pomocné látky; celulosa; 3D tisk; benzydamin; Printing, Three-Dimensional; Benzydamine; vysoušení; farmaceutická technologie; Viscosity; Excipients; Drug Delivery Systems; Cellulose; Technology, Pharmaceutical; lékové transportní systémy; Desiccation; viskozita